Enunciado

EQUAÇÃO DE BESSEL

Nos Problemas 1-6, utilize (1) para encontrar a solução geral da equação diferencial dada em ( 0 , ∞ ) .

x 2 y ' ' + x y ' + x 2 - 1 y = 0

Passo 1

Nos Problemas 1-6, utilize (1) para encontrar a solução geral da equação diferencial dada em ( 0 , ∞ ) .

x 2 y ' ' + x y ' + x 2 - 1 y = 0

Passo 2

P o n t o   s i n g u l a r   i r r e g u l a r   :   x = 1 .   P o n t o   s i n g u l a r   r e g u l a r :   x = 0 .

Resposta

P o n t o   s i n g u l a r   i r r e g u l a r   :   x = 1 .   P o n t o   s i n g u l a r   r e g u l a r :   x = 0 .